Religion and worldviews in 1944 and 2021: a sociological analysis of religious education in two sociohistorical contexts - Sharpe, Keith (Journal of Religious Education, 2021)
Religious education was established as a compulsory curriculum requirement in all schools by the 1944 Education Act. It was intended to provide instruction to all pupils in the basic tenets of the Christian faith and ensure that every successive generation of pupils understood the role of Christianity in British history and the national sense of British identity. In examining the sociohistorical context in which this groundbreaking education act emerged it is evident that at that time religious education had a very clear purpose and unambiguous raison d'être. It was a key element in the socialisation process of children which familiarised them with the prevailing societal norms of behaviour, social values and dominant beliefs. By the second decade of the twenty-first century this certainty about a rationale for RE had been lost. Widespread confusion had developed about what the point of religious education actually was, and inspections of RE teaching revealed the subject to be in a parlous state (OFSTED in: Religious education: realising the potential, 2013; in: School inspection handbook, 2019). In 2016 the Religious Education Council of England and Wales established the Commission on Religious Education (CoRE) in an attempt to bring some clarity back into the subject. In the years between 1944 and 2021 social norms, values and beliefs had changed significantly and consequently the world RE teachers were seeking to socialise children into was and is very different. The solution proposed by the CoRE is to concentrate on teaching 'worldviews' to prepare pupils to respect the diversity of beliefs in contemporary society. Far from saving the subject, however, this shift of focus can be seen in many ways which are explored in this paper to be more likely to hasten the end of RE as a curriculum subject and to accelerate its replacement by an enhanced form of citizenship education.